The Role of Islamic Education Teachers in Fostering the Habit of Congregational Prayer at SD Bintang Bontang - Muchammad Aminudin; Moh Salehuddin; M. Tahir (Universitas Muhammadiyah Enrekang, 2023)
The purpose of this study was to determine the role of PAI teachers in fostering the habit of congregational prayer at SD Bintang Bontang. The type of research used is qualitative research, with primary data sources and skunder. The results of this study show that 1) congregational prayers will remind students and teachers to stick to religious principles amidst the challenges of secular life. No matter how busy students are pursuing worldly ideals through educational media, it does not mean they have to be far from Ukhrawi ideals. This is how the religion of Islam teaches, and 2) congregational prayer activities can also minimize juvenile delinquency at school. Psychologically, students will feel watched and fortified by the prayers they do.